"Thinking Beyond Borders"? A Transnational Feminist Critique of Discourses of Internationalism in Canada - Cairns, Kate (Atlantis)

(untitled) (Mount Saint Vincent University, 2010)
This paper presents a transnational feminist critique of discourses of internationalism in Canada by analyzing a speech delivered at the 2008 Congress of Humanities and Social Sciences. The paper explores how feminist discourses are sometimes mobilized in defense of dominant (inter)national narratives and argues in support of transnational feminist interventions.